The effects of postponing BCG vaccination on the risk of BCG-related complications among patients with severe combined immunodeficiency disease in Saudi Arabia - Aldhaheri, Amal; Alyabes, Ohoud; Aljumaah, Suliman; Alhuthil, Raghad; Alonazi, Raghad; Alamoudi, Shefa; Alsuhaibani, Mohammed; Alghamdi, Salem; Albanyan, Esam A.; Al-Hajjar, Sami; Mohammed, Reem; Arnaout, Rand; et al. (Frontiers in Immunology, 2025)
IntroductionThe Bacillus Calmette–Guérin (BCG) vaccine is widely used to prevent tuberculosis but is associated with significant complications in patients with severe combined immunodeficiency (SCID). Considering the high incidence of SCID in Saudi Arabia, the Ministry of Health revised its national vaccination schedule in 2019, postponing BCG administration from birth to 6 months of age, aiming to enable time for the diagnosis of primary immunodeficiency diseases before vaccination. This study evaluated the consequences of this policy change on the incidence of BCG-related complications in SCID patients.MethodsThis retrospective study included 178 SCID patients diagnosed at King Faisal Specialist Hospital and Research Center, Riyadh, between 2015 and 2023. Patients were divided into two cohorts: Era 1 (2015–2019), when BCG vaccination was administered at birth, and Era 2 (2019–2023), when BCG vaccination was administered at 6 months of age. Data on demographics, clinical presentations, BCG-related complications, genetic testing, treatment, and outcomes were analyzed.ResultsA total of 49 SCID patients developed BCGitis, of which 65.3% experienced disseminated disease. The incidence of BCG-related complications dropped significantly after the policy change, from 46.1% in Era 1 to 2.6% in Era 2. Patients required stem cell transplantation and a median of 17.6 months of anti-mycobacterial therapy. The crude mortality rate was high (36.7%; 18/49), with 66.7% (12/18) of these fatalities linked to disseminated BCGitis.ConclusionsPostponing BCG vaccination to 6 months of age significantly decreases the incidence of BCG-related complications in SCID patients and highlights the importance of tailoring vaccination schedules for high-risk populations. Early newborn screening and timely diagnosis of immunodeficiencies are essential to further minimize complications. The revised vaccination policy of Saudi Arabia provides a model for optimizing immunization strategies in regions with a high prevalence of inborn errors of immunity.